Enhanced microwave catalytic-esterification of industrial grade glycerol over Brønsted-based methane sulfonic acid in production of biolubricant - Kong, P.S.; Aroua, M.K.; Daud, W.M.A.W.; Cognet, P.; Pérès, Y. (Institution of Chemical Engineers, 2016)
The industrial production of renewable lubricant glycerol trioleate was simulated using a microwave reactor through esterification of glycerol with oleic acid in the presence of methane sulfonic acid catalyst under solvent-free conditions. The interaction effects of operating temperature, catalyst concentration, and reaction time were investigated. A conversion of 90% was achieved in optimal conditions (191 °C, 0.3 wt% and 104 min reaction time) and reduced pressure environment. This result was impressive, compared to the conversion abounded with conventional reactor (39.5%). Furthermore, two different industrial grade crude glycerols were used as starting materials to evaluate the effect of impurities. The findings confirmed that the presence of impurities reduced both selectivity and total conversion significantly.